Impact of polyvascular disease on the prognosis of acute coronary syndrome. (14th October 2021) - Laraba, N; Menzou, F; Aitali, M; Krim, M; Berrah, A
Abstract: : The polyvascular disease reflects a diffuse atherosclerotic disease. By a prospective and descriptive study, recruiting three hundred thirty-six inpatient coronary care unit for acute coronary syndrome, the aim is to estimate the prevalence, to identify predictors factors and to assess the impact of the polyvascular disease in term of mortality and cardiovascular events (MACE 4points) at one, six and twelve months after discharge. The polyvascular disease is defined by the presence of cerebrovascular disease or peripheral artery disease. The cerebrovascular disease is defined in patients with documented stroke or carotid stenosis assessed by ultrasound; the peripheral artery disease is defined by an anchle brachial index (ABI) inferior to 0.9. The prevalence of polyvascular disease in patients with acute coronary syndrome (Men = 69, 0%; mean age = 63, 3y) is 28.9%. In our study population, 20.8% have cerebrovascular disease. A significant carotid stenosis is seen in 57 patients (16, 7%), half of which have bilateral stenosis. 16.1% of patients have a peripheral artery disease. an ABI less than 0.45 is found in 7 patients (2, 1%). 1.8% of patients have abdominal aortic aneurysm. Many factors statistically associated with the polyvascular disease are identified. High blood pressure, thinness, advanced age, prolonged smoking and diabetes are the most powerful predictors. On admission, the polyvascular patients have more likely a KILLIP than or equal to two, anemia and kidney failure. They have an ejection fraction of the left ventricle lower than patients with only coronary artery disease. Their coronary artery disease appears more severe and extensive in coronary angiography. Polyvascular disease appears as an independent and powerful predictor of mortality and cardiovascular events in the short and medium term in patients with acute coronary syndrome. The hazard ratio of polyvascular disease mortality at day 30, 6 months and 12 months of hospitalization are respectively 6.16, 4.44 and 5.91. The hazard ratio for disease polyvascular for cardiovascular events at 6 months and 12 months of hospitalization are 2.79 and 2.90 respectively. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): University hospital of Bab ElOued AlgiersUniversity hospital of Douéra Algiers